Innocuous presentation of low-grade mucoepidermoid carcinoma of the palate - Thilak T John; Manisha M Khorate; Nivedita Chinam; Poonam R Sawant (Wolters Kluwer Medknow Publications, 2020)
Mucoepidermoid carcinoma (MEC) is a malignant epithelial tumor and is the most common minor salivary gland neoplasm. The initial presentation of this pathology can resemble benign lesions and can be misleading. They often present as asymptomatic swellings along minor salivary gland bearing areas. Proper attention to clinical features and the use of advanced imaging is of paramount importance to detect these innocuous lesions. We report an incidental finding of a palatal swelling in a 27-year-old female. This paper reports a low-grade MEC with unremarkable clinical features showing underlying bone involvement. It highlights the need for decisive investigations and accurate diagnosis in cases of malignant tumors of the minor salivary glands as it can reduce morbidity and prevent mortality.